Microbial diversity in an intensively managed landscape is structured by landscape connectivity. Issue 10 (18th September 2017) - Griffin, James S.; Lu, Nanxi; Sangwan, Naseer; Li, Angang; Dsouza, Melissa; Stumpf, Andrew J.; Sevilla, Tiffany; Culotti, Alessandro; Keefer, Laura L.; Kelly, John J.; Gilbert, Jack A.; Wells, George F.; et al.
Abstract: Intensively managed land increases the rate of nutrient and particle transport within a basin, but the impact of these changes on microbial community assembly patterns at the basin scale is not yet understood. The objective of this study was to investigate how landscape connectivity and dispersal impacts microbial diversity in an agricultural-dominated watershed. We characterized soil, sediment and water microbial communities along the Upper Sangamon River basin in Illinois—a 3600 km 2 watershed strongly influenced by human activity, especially landscape modification and extensive fertilization for agriculture. We employed statistical and network analyses to reveal the microbial community structure and interactions in the critical zone (water, soil and sediment media). Using a Bayesian source tracking approach, we predicted microbial community connectivity within and between the environments. We identified strong connectivity within environments (up to 85.4 ± 13.3% of sequences in downstream water samples sourced from upstream samples, and 44.7 ± 26.6% in soil and sediment samples), but negligible connectivity across environments, which indicates that microbial dispersal was successful within but not between environments. Species sorting based on sample media type and environmental parameters was the dominant driver of community dissimilarity. Finally, we constructed operational taxonomic unit association networks for each environment and identified a number of co-occurrence relationships that were shared between habitats, suggesting that these are likely to be ecologically significant. Abstract : Beta diversity differed between up- and downstream microbial communities for soil, sediment and water samples based on landscape connectivity and ease of dispersal between sites.